Community engagement: Universities' roles in building communities and strengthening democracy. Issue 5 (19th October 2016) - Cook, James R.; Nation, Maury
Abstract: Many universities are making concerted efforts to engage their communities as part of their effort to strengthen democratic principles and processes. These initiatives have included faculty and students assuming both traditional and novel roles to promote community engagement, with varying degrees of success. This article examines university engagement strategies through the lenses of community psychology and community development to identify challenges and opportunities in teaching, research, and service to promote democratic ideals. Specific examples of university practices that engage the community and vary in the advancement of democratic principles are outlined, with suggestions for ways that universities can enhance their ability to promote democratic participation.